Strategy of innovative projects management - L. A. Ahmetov; I. A. Vorobiev (Путеводитель предпринимателя)
Innovation in the Russian industry does not always lead to increased business efficiency, thus the quality of innovation for economic development in general, is the question . Therefore, the quality of innovation and quality of innovation deserves special attention. This article describes the objectives, principles and methods of quality management of innovation projects.